1993
DOI: 10.1073/pnas.90.14.6741
|View full text |Cite
|
Sign up to set email alerts
|

A mutant alpha subunit of G12 potentiates the eicosanoid pathway and is highly oncogenic in NIH 3T3 cells.

Abstract: The discovery of GTPase-inhibiting muta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
299
3
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(312 citation statements)
references
References 27 publications
8
299
3
2
Order By: Relevance
“…Activating mutations have also been identi®ed for Ga i2 , referred to as the gip2 oncogene, in a subset of ovarian sex cord stromal tumors and adrenal cortical tumors (Lyons et al, 1990). In addition, Ga 12 , referred as the gep oncogene (Xu et al, 1993(Xu et al, , 1994, was isolated as a transforming gene from a soft tissue sarcoma-derived cell (Chan et al, 1993), although its role in tumorigenesis is still unclear. No naturally occurring activated mutations in members of the Ga q family have been described to date.…”
Section: Oncogenic Potential Of G Protein-coupled Receptorsmentioning
confidence: 99%
“…Activating mutations have also been identi®ed for Ga i2 , referred to as the gip2 oncogene, in a subset of ovarian sex cord stromal tumors and adrenal cortical tumors (Lyons et al, 1990). In addition, Ga 12 , referred as the gep oncogene (Xu et al, 1993(Xu et al, , 1994, was isolated as a transforming gene from a soft tissue sarcoma-derived cell (Chan et al, 1993), although its role in tumorigenesis is still unclear. No naturally occurring activated mutations in members of the Ga q family have been described to date.…”
Section: Oncogenic Potential Of G Protein-coupled Receptorsmentioning
confidence: 99%
“…Rac(7) and ras(7) are each dominant negative mutants which contain the mutation T17N, rendering these proteins unable to bind GTP ( see Feig and Cooper 1988) pathways (Clapham and Neer, 1993). The heterotrimeric G-proteins Gaq, Ga12 and Ga13 are each capable of transforming NIH3T3 cells (Dhanasekaran and Dermott, 1996;Voyno-Yasenetskaya et al, 1994;Chan et al, 1993;Xu et al, 1993;Jiang et al, 1993;Kalinec et al, 1992) and we have previously shown that Gaq but not Ga12 is responsible for transducing m5-induced proliferative responses in NIH3T3 cells (Burstein et al, 1995b;. It has been recently shown that GTPase de®cient mutants of Gaq, Ga12 and Ga13 activate the JNK pathway (VoynoYasenetskaya et al, 1996;Vara Prasad et al, 1995) and we have found that Gaq, Ga12 and Ga13 can each induce proliferative responses in R-SAT TM (Figure 1 and see Burstein et al, 1997).…”
Section: Alpha1bmentioning
confidence: 99%
“…Overexpression of wild-type Ga 12 transforms NIH3T3 cells (Chan et al, 1993), and expression of Ga 12 Q229L or Ga 13 Q226L induces neoplastic transformation in NIH3T3 cells (Xu et al, 1993(Xu et al, , 1994Jiang et al, 1993;Vara Prasad et al, 1994) and Rat-1 cells . In 1321N1 astrocytoma cells, Ga 12 is required for thrombin-induced mitogenesis (Aragay et al, 1995).…”
Section: Introductionmentioning
confidence: 99%